MENINGKATKAN KEMAMPUAN GURU DALAM MENGAJAR MATEMATIKA MELALUI BIMBINGAN BERKELANJUTAN DI SD 2 SUMBERAGUNGTAHUN PELAJARAN 2017/2018 - Martono . (Universitas PGRI Yogyakarta, 2018)
This scrutiny aim to do a approach towards education process starting from school expansion article, education intelligence implementation floor education ones and evaluationand supervision towards man, money, materials, methode and machine in floor educationones in SD 2 Sumberagung. This Scrutiny type isScrutinySchool Action, Scrutiny Procedur isas subjectTeacher School class I - VI in SD 2 (two) Sumberagung, steps that on by wearing 2siklus. Every siklus uses jigsaw model in matematika learning in class I - VI SD 2Sumberagung. Every siklus in this scrutiny comprise on planning activity, action perception,andreflectionoverthemove. ScrutinySumming is result 1) Supervisi learning needs to be done by kontinyu byheadmaster, and or monitor, for interest launch him road him learning. 2) Pelatihan classteacher snarl with basic concept calculate really support efektifitas operation deliveryefficacy calculate in matematika subject. 3) Matematika learning in standar Usingcompetencyfraction in problem break up, really if his teacher and undergraduate controljarimatikaconcept. 4) When teacher control soldering and become visible profesioanal as teacher, anduse carrier media that is enough so pupil feel fluent and like learning process. 5) Matematikalearning required intelligence and teacher patience in framework guide and directundergraduate, so that undergraduate able to grab abovestandar KKM value.Keyword : Enhancing Capacity, Matematika, Guidance